Condensation in Ukrainian home of material and spiritual culture of people (based on phraseology) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In this article semantic range of phraseology to the concept of house considering its direct and symbolic values​​ are set. The importance of native home for the Ukrainians is found out on base of idioms above. The features of the Ukrainian national character reflected in the material are outlined.
Keywords: phrases; concept; components; mentality; culture